What is history for? - Southgate, Beverley C. (Routledge, 2005)
"What is History For? is a timely publication that examines the purpose and point of historical studies. Charting the development of historical studies, Beverley Southgate examines the various uses to which history has been put. While history has often supposedly been studied 'for its own sake', Southgate argues that this seemingly innocent approach masks an inherent conservatism and exposes the ways in which history has, sometimes deliberately, sometimes inadvertently, been used for socio-political purposes. With traditional notions of truth and historical representation now under question, it has become vital to rethink the function of history and renegotiate its uses for the postmodern age. History in the 21st century, Southgate proposes, should adopt a morally therapeutic role that seeks to advance human hope and happiness."--BOOK JACKET.